HYDRAULIC MODELING STUDY OF ALTERNATIVE FLOOD CONTROL STRATEGIES FOR THE REJOSO RIVER PASURUAN - Mohammad Dimas Noor Syamsuddin; Mahendra Andiek Maulana (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2025)
Rejoso River is administratively included in Pasuruan Regency where its watershed is located in 10 sub-districts (Puspo, Tosari, Gondang Wetan, Rejoso, Winongan, Pasrepan, Grati Districts of Pasuruan Regency and Lumbang, Sukapura, Probolinggo Regency). The area of the Rejoso River watershed is ± 361.2 km2, bordered by hillsides and protected forests. In general, the cause of flooding in the Rejoso River watershed is caused by high intensity rainfall and changes in land use such as the Rejoso River, especially in the upstream area. The flat topography of the downstream area causes potential sedimentation which inhibits the flow (run off). The purpose of this study is to determine the condition of the existing system and capacity of the Rejoso River; to determine the influence of land use, and to provide alternative scenarios for the most effective flood control to reduce the flood water level or collect the flood that occurs. In this study, hydrological and hydraulic modeling was carried out. The method that used in the calculation of flood discharge is HEC-HMS, while for hydraulic analysis the HEC-RAS 1D is used with the results of water level at the river cross section. This analysis aims to determine the most effective flood control scenario for reducing flooding that occurs in the Rejoso River. The results of this study are alternative flood control scenarios for the Rejoso River by carrying out normalization, embankment’s structure and retention ponds which are the best scenarios for reducing high flood water levels. This can be shown by a decrease of average height of the flood water level from 1.207 meters to 0.435 meters. With these conditions, it can be concluded that this scenario is the best scenario for reducing the high flood overflow in the Rejoso River.